SOME LAW-ENFORCEABLE ASPECTS OF THE EXECUTION OF CONTRACTS WITH EXCESS OF POWERS IN ECONOMIC RELATIONS - Veronika N. Shkabaro (Alfred Nobel University Journal of Law)
The article is devoted to the consideration and analysis of the main theoretical and law enforcement aspects of transactions with abuse of authority and their subsequent approval in economic relations. The article analyzes certain aspects of legal regulation of invalidity of economic transactions. The author establishes that transactions made without the consent (approval) of an authorized body are disputed transactions. The law establishes that a transaction made by a representative in excess of his or her authority creates, modifies, or terminates the civil rights and obligations of the person he or she represents only if the transaction is subsequently approved by that person. A transaction is deemed to be approved, in particular, if the person represented has taken actions indicating acceptance of the transaction for execution. It is noted that approval of a transaction by a legal entity made by a representative in excess of his/ her authority is considered as a way to eliminate (a type of “healing”) the defects of the transaction. It is determined that approval in judicial practice means not only the adoption of a certain decision by a legal entity’s body, but also the performance of any action or tacit consent. By its legal nature, approval of a transaction by a represented person is a unilateral transaction. It is established that courts dismiss claims if there is evidence of the plaintiff’s approval of the transaction. If the disputed transaction is signed by the parties and after its execution both parties took actions to execute the transaction, this indicates its subsequent approval by the plaintiff. The author establishes that bad faith and unreasonableness of the counterparty are mandatory grounds for invalidating a contract in the absence of the required capacity of a legal entity’s representative. The author establishes that legal practice demonstrates a significant variety of methods and forms of both entering into contracts and approving the actions of a legal entity’s representative. The author proves that approval of a commercial contract is actually considered to be a way of legitimizing a transaction made on behalf of a legal entity by its representative.